DNA damage assessment of human breast and lung carcinoma cells irradiated with protons and carbon ions. Issue 1 (1st January 2020) - Ristic-Fira, Aleksandra M.; Keta, Otilija D.; Petković, Vladana D.; Cammarata, Francesco P.; Petringa, Giada; Cirrone, Pablo G.A.; Cuttone, Giacomo; Incerti, Sebastien; Petrović, Ivan M.
ABSTRACT: Differences in biological response of breast and lung cancer cells to 62 MeV/u therapeutic protons and carbon ions are investigated on MCF-7 and HTB177 cells. Hydroxyl radical scavenger, dimethyl sulfoxide (DMSO) is applied to reduce indirect effects of irradiation, while serum deprivation provided uniformity of cell population. Survival, immunocytochemical, and cell-cycle analysis, changes in protein expression involved in repair and apoptosis are followed. Radiobiological parameters, Bax/Bcl-2 ratio, and increased subG1 fraction show that carbon ions are more efficient in cellular killing than protons. No significant difference in the number of γH2AX foci are found between protons and carbon ions. According to SF2 values, MCF-7 cells are more radioresistant to both ion species compared to HTB177 cells. Cell-cycle analysis and expression of relevant protein markers further confirm somewhat higher radiosensitivity of HTB177 cells compared to MCF-7. DMSO leads to the rise of cell survival and decreases the number of γH2AX foci. Even though there are no significant changes in the number of γH2AX foci after used irradiation types, lesions induced by carbon ions are probably more complex than those produced by protons. DMSO minimizes indirect DNA damage to achieve experimental conditions needed for comparisons of obtained results with numerical simulations.